Cognitive Change during the Life Course and Leukocyte Telomere Length in Late Middle-Aged Men - Rask, Lene; Bendix, Laila; Harbo, Maria; Fagerlund, Birgitte; Mortensen, Erik L.; Lauritzen, Martin J.; Osler, Merete (Frontiers in Aging Neuroscience, 2016)
Abstract Importance: Cognitive skills are known to decline through the lifespan with large individual differences. The molecular mechanisms for this decline are incompletely understood. Although leukocyte telomere length provides an index of cellular age that predicts the incidence of age-related diseases, it is unclear whether there is an association between cognitive decline and leukocyte telomere length. Objective: To examine the association between changes in cognitive function during adult life and leukocyte telomere length after adjusting for confounding factors such as education, mental health and life style. Design, setting and participants: Two groups of men with negative (n=97) and positive (n=93) change in cognitive performance were selected from a birth cohort of 1985 Danish men born in 1953. Cognitive performance of each individual was assessed at age ~20 and ~56 years. Leukocyte telomere length at age ~58 was measured using qPCR. Linear regression models were used to investigate the association between cognitive function and leukocyte telomere length. Results: Men with negative change in cognitive performance during adult life had significantly shorter mean leukocyte telomere length than men with positive change in cognitive performance (unadjusted difference β= - 0.09, 95% CI -0.16 - -0.02, p= 0.02). This association remained significant after adjusting for smoking, alcohol consumption, leisure time activity, body mass index and cholesterol (adjusted difference β= -0.09, 95% CI -0.17 - -0.01, p= 0.02) but was nonsignificant after adjusting for smoking, alcohol consumption, leisure time activity, body mass index cholesterol, current cognitive function, depression and education (adjusted difference β= -0.07, 95% CI -0.16 - -0.01, p= 0.08). Conclusion and relevance: Preclinical cognitive changes may be associated with leukocyte telomere length.